2017
DOI: 10.1155/2017/9248153
|View full text |Cite
|
Sign up to set email alerts
|

C60 Filling Rate in Carbon Peapods: A Nonresonant Raman Spectra Analysis

Abstract: We calculated the nonresonant Raman spectra of C60 peapods to determine the concentration of C60 fullerenes inside single-walled carbon nanotubes. We focus on peapods with large diameters for which C60 molecules can adopt a double helix configuration or a two-molecule layer configuration. Our calculations are performed within the framework of the bond-polarizability model combined with the spectral moment’s method. The changes in the Raman spectra as a function of C60 filling rate and the configuration of C60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The intensities of the Raman lines are calculated within the empirical non-resonant bond polarizability model [19] . In this study we use the same bond polarizability parameters used in our previous work concerning the calculation of the Raman spectra of individual C60 and C70 peapods [12,20] . The D-band in the Raman spectra of sp 2 carbons is a signature of defects in the graphene lattice [21] and is often used to characterize defective SWNTs.…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensities of the Raman lines are calculated within the empirical non-resonant bond polarizability model [19] . In this study we use the same bond polarizability parameters used in our previous work concerning the calculation of the Raman spectra of individual C60 and C70 peapods [12,20] . The D-band in the Raman spectra of sp 2 carbons is a signature of defects in the graphene lattice [21] and is often used to characterize defective SWNTs.…”
Section: Model and Methodsmentioning
confidence: 99%
“…The presence of vacancies may deteriorate the outstanding properties of nanotubes but may also have beneficial effects. In previous works of our group [11,12,13] , we calculated the vibrational properties of non defect C60 peapods. In order to improve the comparison with the experimental Raman data measured on peapod samples, we calculate the nonresonant Raman spectra of C60 filled hexa-vacancy SWNT.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that only one type of orientation can exist for a given nanotube and confirm that the C 70 alignment is associated with the geometrical parameters of the nanotube host. Theoretical studies showed that the configuration of C 70 s inside SWCNT depends primarily on tube diameter and does not significantly depend on tube chirality [21,22]. In order to obtain the optimal structure of the C 70 inside the nanotubes, an energy minimization procedure was performed by Fegani et al (for more detail, see reference [21]).…”
Section: Peapodsmentioning
confidence: 99%
“…More recently, Raman calculations are extended to a larger range of diameters in which C 60 molecules can adopt a double helix and a layer of two molecules [22]. …”
Section: Diameter Dependence Of the Raman Spectrum Of C 60 Peapodsmentioning
confidence: 99%
“…In previous works [23,27,28], we studied the different possible configurations of C 60 and C 70 molecules encapsulated into SWCNTs with diameter lower than 2.28 nm. Raman spectra of C 60 carbon peapods have been calculated for C 60 linear, zigzag, double helix and layer of two molecules configurations within the bond-polarizability model.…”
Section: Introductionmentioning
confidence: 99%